2006
DOI: 10.1063/1.2206149
|View full text |Cite|
|
Sign up to set email alerts
|

Critical Poisson’s ratio for plasticity in Fe–Mo–C–B–Ln bulk amorphous steel

Abstract: Articles you may be interested inInfluence of erbium on the electronic structure of Fe ( 65 − x ) Mo 14 C 15 B 6 Er x ( x = 0 , 1 , 2 ) bulk metallic glasses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
128
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(141 citation statements)
references
References 7 publications
13
128
0
Order By: Relevance
“…2,3,[27][28][29] For metallic glasses that are intrinsically brittle with little or no accumulated strain, they would exhibit far less liquid-like fracture in surface morphologies or diminishing scales in the vein-patterns. 30) Furthermore, the homogeneous deformation as seen in the tensile simulation suggests that the shear localization may not be the only mechanism for deformation in metallic glasses at low temperatures. However, we should realize that maintaining the stringent conditions in experiments as those in the simulation is highly improbable.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,[27][28][29] For metallic glasses that are intrinsically brittle with little or no accumulated strain, they would exhibit far less liquid-like fracture in surface morphologies or diminishing scales in the vein-patterns. 30) Furthermore, the homogeneous deformation as seen in the tensile simulation suggests that the shear localization may not be the only mechanism for deformation in metallic glasses at low temperatures. However, we should realize that maintaining the stringent conditions in experiments as those in the simulation is highly improbable.…”
Section: )mentioning
confidence: 99%
“…This crucial property and its connection to the free volume change are currently under investigation. 30) …”
Section: )mentioning
confidence: 99%
“…13,14 Recently, it was reported that the ductility of BMGs was closely related to their Poisson's ratio. [15][16][17] For example, Ptbased BMG with high Poisson's ratio of about 0.41 shows an excellent compressive ductility. 15 Nivikov and Sokolov 18 reported that Poisson's ratio of a glass at room temperature correlates with the fragility of liquids at high temperature.…”
mentioning
confidence: 99%
“…The Poisson ratio v is considered as an indicator to predicate the ductile-brittle behavior of metallic materials. In some literature, bulk metal glasses are reported to have good ductility with the v > 0.31 [44]. The Poisson ratio of the present HEAs is v = 0.36-0.37.…”
Section: Cubic Elastic Constantsmentioning
confidence: 77%